Relationship between Marital Adjustment and Wellbeing of Married Individuals - Kumcagiz, Hatice; Demir, Yasin; Yılmaz, Mustafa Ecevit (My University, 2020)
The main purpose of this study is to investigate the relationship between marital adjustment levels and psychological well-being levels in terms of certain variables. To this end, it is used a relational survey model to determine the marital adjustment predictor variables of married individuals. In relational studies, correlation and causal comparisons are commonly preferred. Convenience sampling method was used to determine study group. In this method, researchers create the sample by starting from participants that are easily accessed until desired sample size is achieved. For this purpose, 324 participants were reached and measurement tools were employed. The data were collected using Marital Adjustment Scale, Psychological Well-Being Scale and a personal information form. Participants of this study were married individuals with children in Samsun city of Turkey. Among 324 voluntary participants of this study, 158 (48.8%) were females and 166 (51.2%) were males. Age of participants ranged between 21 and 65. The findings showed that marital adjustment significantly predicted psychological well-being. Marital adjustment levels and psychological well-being levels did not differ significantly according to gender. Additionally, depending on the results, a psycho-education plan is proposed to increase the psychological well-being of married individuals.
Keywords: Davranış Bilimleri